Genotype × Environment interaction: AMMI analysis of radish (Raphanus sativus) genotypes in different environments of Punjab - Kaur, Inderdeep; Singh, Rajinder; Singh, Dilbag (The Indian Journal of Agricultural Sciences, 2020)
The study entailed the determination of Genotype × Environment (G × E) interaction through Additive Main effects and Multiplicative Interaction (AMMI) analysis to identify radish (Raphanus sativus L.) genotypes suitable for cultivation in the province of Punjab, India. Twelve newly developed advanced breeding lines of radish were sown on six different dates for two years, i.e. 2014-15 and 2015-2016, in a randomized complete block design, replicated thrice. The explicit analysis of the AMMI revealed pronounced performance differences among the genotypes due to environments, explained by high percentage of GEI through IPCA1 and IPCA2 (65.48 %-82.79%). The AMMI analysis clearly delineated the mega environments and provided information on the cultivars exhibiting enhanced performance in those mega-environments on the basis of stability, performance and genetic difference between genotypes and environments. Temperature and photoperiod were the major contributing factors in G × E interactions. RL-30 excelled across the environments in terms of root length, root weight, plant weight and total marketable yield whilst, RB-21 performed best under hostile environments (high – ve score on IPCA axis).